Review of the sulcacitus group of Euschistus (Pentatomidae: Pentatominae: Carpocorini) with description of the internal female genitalia and a new species - Bianchi, Filipe Michels; Barão, Kim Ribeiro; Grazia, Jocelia (Zootaxa, 2017)
Euschistus Dallas is comprised of 66 species in three subgenera. Species of the nominate subgenus occur mainly in Central and North America. Some groups of species have been proposed to Euschistus (Euschistus) based on general external and male genitalic morphologies. Here, we review the sulcacitus group providing illustrations and descriptions of the internal and external genitalia of both sexes, illustrating females for the first time. A new species, Euschistus (Euschistus) tacitus sp. nov. Bianchi & Grazia, from Mexico and Costa Rica is described. We also provide an identification key to species of the group.